2018
DOI: 10.36108/nje/8102/43(0121)
|View full text |Cite
|
Sign up to set email alerts
|

Termiticidal efficacy of extracts of two indigenous plants against Macrotermes subhyalinus Rambur (Blattodea: Termitidae)

Abstract: The termiticidal potentials of methanol, n-hexane, acetone and water extracts of heart wood of Milicia excelsa (Welw.) C. Berg and leaves of Khaya senegalensis (Desr) and their botanical mixture against Macrotermes subhyalinus (Rambur) attacking Triplochiton scleroxylon (Obeche) wood blocks were evaluated in this study. The trial lasted for 12 weeks in open field and under shade conditions. Visual rating and weight loss determination were used to assess the level of termite damage on treated wood blocks. Treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Some were however harvested from surface termite tunnels at night when they forage for food as well as infested logs of wood. The harvested termites in the study area had earlier been identified as Macrotermes subhyalinus (Rambur) in a study conducted by Ajayi et al (2018). Dark chambers were constructed using the method of Ali, Ahmed, Sheridan, and French (2016) with some modifications.…”
Section: Termite Culturementioning
confidence: 99%
See 4 more Smart Citations
“…Some were however harvested from surface termite tunnels at night when they forage for food as well as infested logs of wood. The harvested termites in the study area had earlier been identified as Macrotermes subhyalinus (Rambur) in a study conducted by Ajayi et al (2018). Dark chambers were constructed using the method of Ali, Ahmed, Sheridan, and French (2016) with some modifications.…”
Section: Termite Culturementioning
confidence: 99%
“…Aqueous extracts of each plant material used in this study were prepared according to the method of Ajayi et al (2018) with little modifications. Powders of each of the three plant parts weighing 10 g were properly admixed together in dual (ratio 1:1) and tricombinations (ratio 1:1:1).…”
Section: Preparation Of Plant Extractsmentioning
confidence: 99%
See 3 more Smart Citations